Sosialiasasi Pembuatan Lubang Resapan Biopori di Kelurahan Malasilen - Indriyani, Nita; Putri, Lydia; Sahuburua, Franklin; Nernere, Samuel; Lumbantoruan, Lusiana (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
Biopore Infiltration Hole is a small hole in the soil that is formed due to the activity of soil organisms such as worms, root movement in the soil, termites and other animals. The hole is filled with air until it enters the water stream. Rainwater does not go directly into the gutter but seeps into the ground through the hole. The benefits of the Biopori Infiltration Hole for the community are: Reducing the impact of floods, landfills for organic waste, fertilizing plants, and improving ground water quality. The expected results from the implementation of this activity are to reduce the impact of flooding in the Malasilen Village area and increase the understanding of residents to recognize the surrounding environment, increase the spirit of community cooperation to overcome problems in their environment, and prevent disease outbreaks due to puddles of drainage water.